Atypical Communication Characteristics, Differential Diagnosis, and the Autism Spectrum Disorder Phenotype in Youth. Issue 2 (3rd March 2020) - Kang, Erin; Gadow, Kenneth D.; Lerner, Matthew D.
Abstract : This study compared atypical communication characteristics (ACCs) in clinic-referred youth with and without autism spectrum disorder (ASD), identified subgroups based on different patterns of ACCs in youth with ASD, and determined if ACC subgroups result in meaningful clinical phenotypes in their relation to psychopathology and functional outcomes. Youth 6–18 years of age ( N = 947; M age = 11.41; 72% male; 84% Caucasian) with and without ASD were assessed using Child and Adolescent Symptom Inventory–4R and the Parent Questionnaire, which included a checklist of ACCs. Prevalence of ACCs was examined and receiver operational characteristic analyses were used to estimate the diagnostic accuracy of number of ACCs for ASD. Latent class analysis was conducted to see if patterns of ACCs yielded clinically useful subgroups in youth with ASD. Youth with ASD exhibited higher rates of ACC than non-ASD psychiatry referrals, and a summary score of ACCs easily differentiated the two clinic-referred samples. Among youth with ASD, ACC subgroups exhibited differences in severity of psychiatric symptoms, ASD symptomatology, and functional outcomes. Our results suggest that ACCs are an important characteristic of the ASD clinical phenotype and may be a useful consideration for defining more precise ASD symptomatology, functional outcomes, and treatment targets.